A Narrative Review of Maternal Nutrition and Early Childhood Development - Arifa Sultana (Utan Kayu Publishing, 2026)
This structured narrative review synthesizes contemporary evidence (2016–2026) on maternal nutrition, pregnancy care, fetal nutrition, placental function, and early childhood development to clarify their integrated roles in lifelong health. Literature was retrieved from MDPI, PubMed, and Cureus using predefined keywords combined with Boolean operators. Peer-reviewed original studies, systematic reviews, and meta-analyses published in English were included, while non-scholarly reports and studies lacking methodological clarity were excluded. Data were narratively synthesized to identify mechanistic and developmental linkages across the first 1,000 days of life. The evidence underscores that adequate maternal nutrition before conception, during gestation, and throughout lactation is fundamental to optimal fetal growth, neurodevelopment, and long-term metabolic programming. Undernutrition, micronutrient deficiencies (e.g., folate, iodine, iron, vitamin D), and maternal hyperglycemia are associated with placental dysfunction, fetal growth restriction, preterm birth, and increased risk of chronic diseases including obesity, type 2 diabetes, and cardiovascular disorders. The placenta emerges as a central regulator of nutrient transport and endocrine adaptation, mediating the effects of maternal metabolic stress on fetal outcomes. Antenatal care utilization, maternal mental health, and socioeconomic determinants further modify developmental trajectories. Evidence also highlights the adverse impact of ultra-processed, proinflammatory dietary patterns and excessive refined sugar intake on maternal metabolic status and offspring health, potentially through inflammatory, oxidative, and epigenetic mechanisms. Optimal early feeding practices that including exclusive breastfeeding for six months and timely introduction of nutrient-dense complementary foods that remain critical for cognitive and physical development. Collectively, findings reinforce that improving maternal nutrition and pregnancy care is essential for reducing intergenerational disease risk and promoting sustainable population health.